PEMANFAATAN ABU BAGASSE SEBAGAI FILLER TERHADAP NILAI MARSHALL TEST PADA CAMPURAN ASPHALT TREATED BASE ( ATB ) - Amal, Andi Syaiful (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Solidity construction of road of Indonesia generally are flexible solidity construction. One ofkind flexible solidity are solidity of ATB ( Asphalt Treated Base ) layer that give fundamental layerfunction that under surface layer which support and spread load along with place to put surfacelayer. Trial to asphalt are follow : penetration, flexible point, ductility, while trial of agregate follow: kind heavy ang agregate absorption, analysis of agregate filler. The thing of test trial of optimumasphalt degree is devided 5 variation namely 5%, 5.5%, 6%, 6.5% and 7% wich each groups aremade 5 different sample with weight each 1200 gram. The optimum asphalt degree which be got6.5%. The thing of test trial of optimum asphalt by filler Bagasse Dust are made 11 groups by fillerdegree 6.42% early which be made 0% up to 90% of Bagasse dust according to weight with 10%interval, by each groups are made 3 samples. The study result showed that three are influence ofusing Bagasse dust as filler to Marshall Test value. Stability is shown by equation Y = 1672.5 +17.544 X – 0.2336 X2 gotten optimum Bagasse dust degree about 37.59% by stability value are2001.033 kg. The flow value is shown by equation Y = 4.05 + ( 2.7 E – 3 ) X – ( 1 E – 4 ) X2 byoptimum Bagasse dust degree about 13.5% is gotten flow value 4.05%. The hole in ATB compoundis shown by equation Y = 4.102 + ( 0.04 ) X – ( 5 E – 4 ) X2 is gotten optimum Bagasse dust about40% by air hole about 4.90%. To Marshall Quotient value may be shown by equation Y = 4.007 +( 0.046 ) X – ( 5 E – 4 ) X2 by optimum Bagasse dust degree about 46% by Marshall Quotient valueare 5.06 kN/mm.Key word : Asphalt Treated Base ( ATB ), Bagasse Dust.